Identification and Characterization of a Novel Plasmodium falciparum Adhesin Involved in Erythrocyte Invasion - Hans, Nidhi (Public Library of Science, 2013)
Malaria remains a major health problem worldwide. All clinical symptoms of malaria are attributed to the asexual blood stages of the parasite life cycle. Proteins resident in apical organelles and present on the surface of P. falciparum merozoites are considered promising candidates for the development of blood stage malaria vaccines. In the present study, we have identified and characterized a microneme associated antigen, PfMA [PlasmoDB Gene ID: PF3D7_0316000, PFC0700c]. The gene was selected by applying a set of screening criteria such as transcriptional upregulation at late schizogony, inter-species conservation and the presence of signal sequence or transmembrane domains. The gene sequence of PfMA was found to be conserved amongst various Plasmodium species. We experimentally demonstrated that the transcript for PfMA was expressed only in the late blood stages of parasite consistent with a putative role in erythrocyte invasion. PfMA was localized by immunofluorescence and immuno-electron microscopy to be in the micronemes, an apical organelle of merozoites. The functional role of the PfMA protein in erythrocyte invasion was identified as a parasite adhesin involved in direct attachment with the target erythrocyte. PfMA was demonstrated to bind erythrocytes in a sialic acid independent, chymotrypsin and trypsin resistant manner and its antibodies inhibited P. falciparum erythrocyte invasion. Invasion of erythrocytes is a complex multistep process that involves a number of redundant ligand-receptor interactions many of which still remain unknown and even uncharacterized. Our work has identified and characterized a novel P. falciparum adhesin involved in erythrocyte invasion.